The bank lending channel: A time-varying approach - Richard Varghese (Graduate Institute of International and Development Studies, 2018)
Using a cross-country panel of 925 banks from 19 advanced economies, for the period 1981-2016, I examine how the bank lending channel of monetary policy has evolved over time. I find that the sensitivity of lending to bank balance sheet liquidity declines over time, with nearly all the reduction occurring between the early 1990s and the early 2000s. Contrary to normal times, during recessions, more liquid banks reinforce the impact of monetary policy shocks on lending relative to their less liquid counterparts. The sensitivity of non-interest income to lending increases sharply from the late 1990s till the global financial crisis of 2008, and declines in the post-crisis period, indicating pro-cyclicality. Moreover, the relative ability of banks with higher non-interest income to mitigate monetary policy shocks increases sharply towards the end of the sample period, capturing the impact of the prolonged low interest rate environment on transmission process. These findings suggest that the structural changes in the banking industry and the state of the economy have a significant impact on the strength of the bank lending channel.
Keywords: E51; E52; E44; 330; bank lending channel; monetary policy; financial regulation